2022
DOI: 10.14202/vetworld.2022.1197-1207
|View full text |Cite
|
Sign up to set email alerts
|

Potential use of Indonesian basil (Ocimum basilicum) maceration to increase estradiol and progesterone synthesis and secretion to improve prenatal growth of offspring using female albino rats as an animal model

Abstract: Background and Aim: Basil is well known as a medicinal plant that contains high essential oils and antioxidant compounds that have the potential to improve ovarian development. Thus, basil may have the potential to improve the growth and development of the uterus and placenta for optimal prenatal growth of offspring. This study aimed to evaluate the effect of Indonesian basil maceration on gonad development of mature female albino rats. Materials and Methods: Fifteen 8-week-old female Sprague-Dawley rats, at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Excess antioxidants result in the body being unable to distinguish between radicals that play a physiological role and radicals that cause oxidative damage to biomolecules. Elimination of all free radicals will not prolong the body's normal functions, but on the contrary, will damage the body's overall performance [23,24]. The increase in FSHr which coincided with the increase in the dose of ethanol extract also did not rule out the possibility of a sign of a polymorphism gene in FSHr due to the appearance of an anomaly at the third dose.…”
Section: Resultsmentioning
confidence: 99%
“…Excess antioxidants result in the body being unable to distinguish between radicals that play a physiological role and radicals that cause oxidative damage to biomolecules. Elimination of all free radicals will not prolong the body's normal functions, but on the contrary, will damage the body's overall performance [23,24]. The increase in FSHr which coincided with the increase in the dose of ethanol extract also did not rule out the possibility of a sign of a polymorphism gene in FSHr due to the appearance of an anomaly at the third dose.…”
Section: Resultsmentioning
confidence: 99%
“…Estrogen directly modulates angiogenesis through its effect on endothelial cells by inducing endothelial proliferation and migration mediated by estrogen receptors [45]. Andrianto et al showed that high concentrations of estrogen and prostaglandins in experimental rats treated with ethanol extract of basil (Ocimum basilicum L) leaves had greater uterine vascularization by increasing VEGF expression [29]. Research by Machado et al stated that severe, very active red endometriosis lesions contained the highest concentration of VEGF compared to mild endometriosis [5].…”
Section: Discussionmentioning
confidence: 99%
“…The mice were housed in a controlled cage with a stable environment, adequate ventilation, and room temperatures of 22oC-25oC. Throughout the study, the mice had access to food and water ad libitum [29]. Mice were divided into 4 groups: the control group (C) and three treatment groups (T1, T2, and T3) receiving ethanol extract of basil leaves at varying doses (0.21 mg/g-BW, 0.42 mg/g-BW and 0.84 mg/g-BW).…”
Section: Animal Models and Research Flowmentioning
confidence: 99%
“…The environment where the mice were placed was regulated by temperature and humidity according to the temperature between 22-25 ᵒC and humidity between 45-65%. Feeding and access to drinking water during the study were given ad libitum [15,19].…”
Section: Animalmentioning
confidence: 99%
“…This could be due to the content of phytochemical compounds such as euginal, euginol, sitosterol, ursolic acid, and stigmasterol in basil leaves which act as phytoandrogens or phytoestrogens [45]. Basil leaves (Ocimum basilicum L.) contain orientin, vicenin, and isoflavones which are estrogenic which can increase exogenous estrogen, bind to estrogen receptors in the body, and proliferate the uterus [19,46,47]. Isoflavones can cause an estrogen-raising effect in many tissues.…”
Section: Pge2 Levelsmentioning
confidence: 99%